Has China’s Housing Security Policy Affected the Housing Market?—Analysis Based on Housing Market Data from 35 Monitored Cities - Guangjun Deng; Weihan Zhou; Dingxing Wang (Buildings)
This study investigates how China’s affordable housing policies have shaped the real estate market, using data from 35 major cities between 2010 and 2023. By analyzing housing prices, sales, and investment trends with advanced statistical methods, we found that increasing the supply of affordable housing significantly slows down rising home prices, especially in cities with high housing costs. During the COVID-19 pandemic, these policies also helped stabilize the market by boosting housing sales and reducing price volatility. Our research highlights regional differences: affordable housing works best in economically developed eastern cities to curb prices, while in less-developed central and western areas, it may temporarily increase prices due to land competition. We also show that affordable housing absorbs demand from low- and middle-income buyers, easing pressure on commercial housing markets over time. This study provides practical insights for policymakers to design targeted housing strategies, optimize land use, and enhance urban resilience during crises, like pandemics. By combining real-world data with robust analysis, we offer a clearer picture of how housing security policies can balance market stability and affordability in rapidly urbanizing economies.